Mathematical methods for science students - Stephenson, Geoffrey (London, United Kingdom : Longman Scientific and Technical, 1975)
This book presents a course of mathematics suitable for undergraduate students of physical science, and has grown out a course of lectures given by the author at imperial college during the past five years.
1. Real numbers and functions of a real variable -- 2. Inequalities -- 3. Limits, continuity and differentianility -- 4. Indefinite, definite and improper integrals -- 5. Convergence of infinite series -- 6. Taylor and maclaurin series -- 7. Complex variable -- 8. Hyperbolic functions -- 9. Partial differentiation -- 10. Differentiation and integration of integrals.
Includes index.
Keywords: HISTORICAL GEOLOGY